Clinical challenges to the concept of ectogestation - Wozniak, Phillip S. (Journal of medical ethics, 2023)
Since the publication of the successful animal trials of the Biobag, a prototypical extrauterine support for extremely premature neonates, numerous ethicists have debated the potential implications of such a device. Some have argued that the Biobag represents a natural evolution of traditional newborn intensive care, while others believe that the Biobag would create a new class of being for the patients housed within. Kingma and Finn argued in Bioethics for making a categorical distinction between fetuses, newborns and ‘gestatelings’ in a Biobag on the basis of a conceptual distinction between ectogenesis versus ectogestation. Applying their arguments to the clinical realities of newborn intensive care, however, demonstrates the inapplicability of their ideas to the practice of medicine. Here, I present three clinical examples of the difficulty and confusion their argument would create for clinicians and offer a possible remedy: namely, discarding the term ‘artificial womb’ in favour of ‘Biobag’.